EIN LOGOS FÜR DAS SEIN UND DEN GOTT. HEIDEGGERS AUSEINANDERSETZUNG MIT DER THEOLOGIE AB DEN DREIßIGER JAHREN - Rosa Maria MARAFIOTI (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
A Logos for Being and God. Heidegger’s Confrontation with Theology from the 1930s. I. Heidegger’s entire itinerary is characterised by the search for a living relationship with God, and thus for a Logos able to think and name the divine without objectifying its divinity. Heidegger’s theological heritage is crucial for his development of the question of Being. Although Heidegger characterizes philosophy as a-theistic in principle already in 1922, he continues to consider of great importance a dialogue with a kind of theology that does not objectify God by means of a dogmatic doctrinal system. Distancing himself from neo-scholastic theology, which makes use of Aristotelian notions based on traditional metaphysics, and that, therefore, should be destroyed, at the end of the 1920s Heidegger assigns to his existential ontology a corrective role towards theology as science of faith. However, from the 1930s onwards he deems it impossible to talk about God until the forgetfulness of the truth of Being is overcome. For this reason, Heidegger understands as task of his thinking the preparation of an authentic experience of divinity. Consequently, he defines his meditation as corrective for thinkers and theologians who pretend to exceed the limits of philosophy and theology and who, failing to differentiate the two, end up believing in Being and conceptualizing God.